2002
DOI: 10.1002/app.10780
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of SiO2 nanoparticle filled–phthalazine ether sulfone/phthalazine ether ketone (50/50 mol %) copolymer composites

Abstract: SiO 2 nanoparticle filled-poly(phthalazine ether sulfone ketone) (PPESK) composites with various filler volume fractions were made by heating compression molding. The tribological behavior of the PPESK composites was investigated using a block-on-ring test rig by sliding PPESK-based composite blocks against a mild carbon steel ring. The morphologies of the worn composite surfaces, wear debris, and the transferred films formed on the counterpart steel surface were examined with a scanning electron microscope, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Poly(phthalazine ether sulfone ketone) (PPESK) copolymer with an equivalent molar ratio of sulfone to ketone is an attractive matrix material because of its high‐temperature stability, its excellent mechanical properties, its radiation and hydrolytic resistance, and its easy processing 16. Because of these advantages, it has received considerable attention in tribological research 17, 18. It has been found that unfilled PPESK possesses a higher friction coefficient and wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(phthalazine ether sulfone ketone) (PPESK) copolymer with an equivalent molar ratio of sulfone to ketone is an attractive matrix material because of its high‐temperature stability, its excellent mechanical properties, its radiation and hydrolytic resistance, and its easy processing 16. Because of these advantages, it has received considerable attention in tribological research 17, 18. It has been found that unfilled PPESK possesses a higher friction coefficient and wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to investigate the tribological behaviors of the micrometer particle‐filled polymer composites, and several mechanisms have been suggested to demonstrate the action mechanisms of fillers 8, 9. It should be noticed not much literature is available that has dealt with nanoparticle‐filled polymers for tribological applications;10–12 however, what has been reported seems to show promise. The nanoparticles have the capability of blending well with polymer, which could lead to strengthening of the transfer film.…”
Section: Introductionmentioning
confidence: 99%
“…3. The major vibrational structures associated with the QAPPESK membrane 11 are found in all the two samples. The peak at 1240 cm −1 is attributed to the stretching vibration of C-O-C, and 1666 cm −1 is assigned to the stretching vibration of the Ar-CvO.…”
Section: Resultsmentioning
confidence: 91%
“…The peak at 1240 cm −1 is attributed to the stretching vibration of C-O-C, and 1666 cm −1 is assigned to the stretching vibration of the Ar-CvO. 11 For the QAPPESK/H 3 PO 4 membrane, the intense peak at 998 cm −1 and small peak at 880 cm −1 are due to the stretching vibrations of PvO for H 3 PO 4 and P͑OH͒ 2 for H 2 PO 4 − , respectively. 12 This indicates that H 3 PO 4 can be combined with QAPPESK in QAPPESK/H 3 PO 4 composite membrane.…”
Section: Resultsmentioning
confidence: 98%